2001
DOI: 10.1111/0938-8982.00023
|View full text |Cite
|
Sign up to set email alerts
|

Predicting, Explaining, and Preventing Children's Reading Difficulties

Abstract: Several decades of research have made it clear that by the time children enter school they already vary widely in their reading-related knowledge and skills. How well do these differences predict differences in reading acquisition? What can they tell us about the causes of reading disabilities? How might these research findings be used to reduce the number of children who have difficulty learning to read? Answers to such questions are fundamental for designing early interventions for children at risk. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
138
1
21

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(167 citation statements)
references
References 52 publications
7
138
1
21
Order By: Relevance
“…The results of the present study suggest that measures of phonological processing and naming speed may be useful in identifying adults with RD, although the inclusion of measures of naming speed does not provide additional diagnostic information independently of reading rate and vocabulary. The results of the present study are mixed at best and are consistent with the conclusions of McCardle et al (2001) that support for the doubledeficit hypothesis of dyslexia remains limited.…”
Section: Discussionsupporting
confidence: 83%
“…The results of the present study suggest that measures of phonological processing and naming speed may be useful in identifying adults with RD, although the inclusion of measures of naming speed does not provide additional diagnostic information independently of reading rate and vocabulary. The results of the present study are mixed at best and are consistent with the conclusions of McCardle et al (2001) that support for the doubledeficit hypothesis of dyslexia remains limited.…”
Section: Discussionsupporting
confidence: 83%
“…Many studies have shown that reading success is associated with reading-related knowledge and skills children have acquired prior to coming to school (see McCardle, Scarborough, & Catts, 2001) and the quality of the home environment during school (e.g., Molfese, Molfese, Key, & Kelly, 2003). Our own prior research suggests that these measures operate largely through shared environmental pathways in early childhood (Petrill, Deater-Deckard, Schatschneider, & Davis, 2005;Seidman et al, 2005), but the effect sizes of these measures are generally small and dissipate after children master decoding skills (Scarborough, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we obtained those articles that had been cited in previous reviews (e.g., McCardle et al, 2001) but did not come up in our formal search. Our complete search generated 36 articles relevant to the double-deficit hypothesis of developmental dyslexia (8 theoretical articles and 28 empirical studies).…”
Section: Criteria and Standards For Article Selectionmentioning
confidence: 99%